The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/128_2012_361
|View full text |Cite
|
Sign up to set email alerts
|

Twisted Arenes

Abstract: The nonbonded steric interactions of substituents at the crowded C4 and C5 positions of phenanthrene cause the aromatic system to twist out of planarity. Similarly, the presence of substituents at the C1 and C12 positions of benzo[c]phenanthrene and at the C1 and C14 positions of dibenzo[c,g]phenanthrene are responsible for the helical twists of the aromatic frameworks. Highly substituted acenes, such as octamethylnaphthalene and decaphenylanthracene, also exhibit substantial end-to-end twists. The X-ray struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 96 publications
(134 reference statements)
1
4
0
Order By: Relevance
“…This demonstrated that the half-life of racemization (in toluene at 85 °C) is 24 h, and the racemization barrier was determined to be 31.0 kcal/mol at 298 K (Figures S13 and S14), which is in good agreement with the DFT calculations. Furthermore, the barrier for the helical inversion of 3c is remarkably high compared to 4,5-diphenylphenanthrene ( 1 ) (Δ G ⧧ = 22.1 kcal/mol, Figure S7), which is in line with reports that 4,5-bis­(4-ethylphenyl)­phenanthrene racemizes fairly rapidly in the solution above 50 °C . These results demonstrate that the twisted structure can enhance the axial chirality of the 4,5-diphenylphenanthrene subunit to create a shape-persistent macrocycle.…”
Section: Resultssupporting
confidence: 87%
“…This demonstrated that the half-life of racemization (in toluene at 85 °C) is 24 h, and the racemization barrier was determined to be 31.0 kcal/mol at 298 K (Figures S13 and S14), which is in good agreement with the DFT calculations. Furthermore, the barrier for the helical inversion of 3c is remarkably high compared to 4,5-diphenylphenanthrene ( 1 ) (Δ G ⧧ = 22.1 kcal/mol, Figure S7), which is in line with reports that 4,5-bis­(4-ethylphenyl)­phenanthrene racemizes fairly rapidly in the solution above 50 °C . These results demonstrate that the twisted structure can enhance the axial chirality of the 4,5-diphenylphenanthrene subunit to create a shape-persistent macrocycle.…”
Section: Resultssupporting
confidence: 87%
“…Bottom-up synthetic efforts toward well-defined, nanosized polycyclic aromatic hydrocarbons (PAHs) have captured the attention of chemists for many years because of their interesting optical and electronic properties, making them of interest for a host of applications . Compared to planar PAHs, nonplanar PAHs, such as circulenes, helicenes, and twisted acenes (as shown in Figure a), show a variety of fascinating molecular packing and structures due to their curved π-electron system. Helicene-like molecules are an interesting class of nonplanar PAHs that can be defined as ortho-fused PAHs, and the deviation of planarity is a result of intramolecular steric repulsion.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of these circulenes changes from a bowl ([5]circulene) to a plane ([6]circulene) and then finally to a saddle ([7]circulene). Theoretical studies indicated that the strain energy of these circulenes, using [6]circulene as a strain-free reference, follows the order: [7]circulene. [27] Although investigations of [4]circulene remain theoretical, tetrabenzo[4]circulene 16 has recently been acquired and identified as a bowl-shaped molecule.…”
Section: [8]circulenesmentioning
confidence: 99%
“…[1] Geometrically, planar PAs can be extended from acenes [2] via condensed arenes [3] or nanoribbons [4] to graphenes. [5] Deformation of a planar structure caused by steric crowding between substituents or an angular arrangement of the aromatic backbone generates twisted PAs [6] or helicenes, [7] respectively. Strain accumulation through the bridge connecting two nonadjacent positions on an aromatic ring makes a cyclophane containing a bent conformation.…”
Section: Introductionmentioning
confidence: 99%